Automated and High-Throughput Urine Drug Screening Using Paper Spray Mass Spectrometry. Issue 2 (22nd July 2022) - Rydberg, Magnus; Dowling, Sarah; Manicke, Nicholas E
Abstract: Paper spray mass spectrometry (PS-MS) has been shown to be a rapid, simple and inexpensive alternative to traditional forensic drug screening methods. It can address the limitations of both immunoassays and chromatography-based techniques due to its non-reliance on sample preparation and its ability to rapidly screen for a wide array of compounds. In this study, an automated PS-MS system was employed to semi-quantitatively screen for 40 commonly abused drugs and metabolites in urine after a 15-min glucuronidase reaction. The target compounds included common prescription opioids, fentanyl and norfentanyl, stimulants including methamphetamine and cocaine, benzodiazepines and antidepressants. The enzyme, buffer and internal standard solution were combined in one spiking solution to minimize sample handling. Analysis was carried out using a commercially available automated paper spray system coupled to a triple quadrupole mass spectrometer. This method may prove useful for clinical and forensic toxicology laboratories as it allows for automated screening of complex samples for drugs without extraction, separation and sample cleanup.